The Effectiveness of Non-Ionizing Radiation Protective Clothing: A Computational Study - Zhara Hajizadeh Bakhtiari; Mehrdad Saviz (AUT Journal of Electrical Engineering)
Exposure protective clothing has been suggested as a protection against RF and microwave electromagnetic fields, especially for pregnant women. These clothings are usually made of metal-woven fabrics. In this article, we use computer simulation methods with a homogeneous human model and plane wave exposure at different polarizations and wave incidence angles over a wide range of frequencies to inspect if a typical anti-exposure clothing model might fail to reduce the fields inside the body under certain exposure conditions and/or at some frequencies. Indeed, as far as our model and computational study can represent actual conditions, it is found that for waves incident along the body axis (as arises e.g. in the sleeping status against a cell-phone tower) the clothing might not only fail to reduce the penetration of EM fields, but can rather increase the electric field intensity in certain body areas, including the abdominal parts which were intended to be protected during pregnancy. We conclude that more physics-aware designs should be employed for such clothing.